2010
DOI: 10.4194/trjfas.2010.0417
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The agarophyte Gracilaria verrucosa (Hudson) Papenfuss was cultivated under greenhouse conditions in Modified Johnson Medium over a 5-month period. Biomass productivity ranged between 5.00 g L -1 to 16.37 g L -1 and the highest biomass was obtained in December. Relative growth rate (RGR) varied from 4.03±1.63 to 1.21±0.34% day -1. While the highest percentages of protein were found in December (20.28±0.94% of dw), the lowest percentages were in March (14.99±0.14% of dw). Phosphorus content ranged from 101.66±3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Thus, it can be said that Özen Spring water can be used for drinking water supply with advanced or appropriate treatment, recreational purposes and aquaculture outside of rainbow trout. The orto-phosphate values obtained in the present study is normal for aquatic ecosystems within recommended range of 0.05-0.3 mg/L (Cirik and Cirik, 2008). According to Bulut et al, (2011) when phosphate concentration is over that 0.3 mg/L, it means that eutrophication occurs in lake.…”
Section: Resultssupporting
confidence: 69%
“…Thus, it can be said that Özen Spring water can be used for drinking water supply with advanced or appropriate treatment, recreational purposes and aquaculture outside of rainbow trout. The orto-phosphate values obtained in the present study is normal for aquatic ecosystems within recommended range of 0.05-0.3 mg/L (Cirik and Cirik, 2008). According to Bulut et al, (2011) when phosphate concentration is over that 0.3 mg/L, it means that eutrophication occurs in lake.…”
Section: Resultssupporting
confidence: 69%
“…In the present study, chlorophyll-a concentrations were estimated between 0.46 and 349.2 µg/L and the average was 23.59 µg/L. It was expressed that chlorophyll-a concentrations between 5 and 140 µg/L indicates an eutrophic lake [40]. High levels of chlorophyll-a concentration, which shows hypereutrophic conditions, were measured in station 3 in autumn when the maximum concentrations of NO 3 were recorded in the lagoon.…”
Section: Discussionmentioning
confidence: 43%
“…A study conducted by [Cirik et al, 2010] showed that G. gracilis had a wide salinity tolerance range, and the optimum production was determined at 42‰ salinity. Moreover, [Özen et al, 2018] found that G. gracilis grows well in the salinity ranges between 25‰ and 35‰.…”
Section: Salinitymentioning
confidence: 99%